A case of postpsychotic depression improved by switching antipsychotic monotherapy. Issue 1 (8th December 2022) - Oguchi, Yoshiyo; Nakagawa, Atsuo; Kocha, Hiroki
Abstract: Aim: Postpsychotic depression is challenging to differentiate, yet it is clinically frequent, puts patients at risk for suicide, and affects their mental capacity. Treatment with antipsychotics for postpsychotic depression is desirable; however, there is no consensus on which antipsychotics are optimal. Case presentation: We report the case of a young male patient with schizophrenia in his 20s who developed postpsychotic depression, including despair, overwhelming loss, humiliation, and suicidal ideation during treatment with paliperidone. As a result, we switched his medication to lurasidone, which relieved his depressive symptoms without any symptom relapse and his social functioning improved. Conclusion: Postpsychotic depression has more psychic characteristics than behavioral. According to various international guidelines for the pharmacological treatment of schizophrenia, antipsychotics should be administered for depressive symptoms of schizophrenia. As evidenced in this case report, lurasidone may be a practical alternative for improving postpsychotic depression. Abstract : Lurasidone monotherapy improves postpsychotic depression in a young man.